Engine lubrication system model calibration and fidelity - Tsobanoglou, Christian; Tsobanoglou, Simon (My University, 2023)
In the present day, tough competition in the automotive industry and shorter timelines for the introduction of new passenger vehicles have forced vehicle manufacturers to cut down on de velopment time. Virtual simulations help in shortening the time vastly and increase efficiency in the development phase avoiding unnecessary waste. The engine is one of the most impor tant subsystems of a car making up the heart of any combustion-driven vehicle, the blood of this engine being the oil, making the lubrication system one of the most critical parts of any engine. With the help of today’s advanced technology, computer software programs like GT-Suite can be used to simulate and predict the oil’s behavior inside an engine in a rather accurate way. This report explores the calibration and validation process of a turbocharged four cylinders engine’s oil system and analyses its accuracy at steady- state conditions. A model of the engine’s oil system is given and the calibration process begins where nine dif ferent calibration parameters, i.e, oil flow rate multiplier, orifice hole diameters, thicknesses, and pressure drop multiplier are used. These are eventually reduced to just two parameters. The calibration process is carried through at a high main gallery pressure mode at tempera tures of 60 and 130 ◦C. Moreover, the system sensitivity is tested where different parameters like the bearing clearances and engine load among others are changed to see their effect on the simulations’ accuracy and time. The model is then validated at all pressure levels and differ ent temperatures. Successful calibration and tuning of the model have yielded highly accurate results in a rea sonably short computational time, thus achieving the most relevant part of this project.
Keywords: Accuracy; Calibration parameters; Engine lubrication system; Flow; GT-Suite; Lubrication; Oil circuit; Pressure